In vitro activities of glycoalkaloids from the Solanum lycocarpum against Leishmania infantum - Clementino, Leandro da Costa [UNESP]; Velásquez, Angela Maria Arenas [UNESP]; Passalacqua, Thais Gaban [UNESP]; de Almeida, Leticia [UNESP]; Graminha, Marcia A.S. [UNESP]; Martins, Gilmarcio Z.; Salgueiro, Lígia; Cavaleiro, Carlos; Sousa, Maria do Céu; Moreira, Raquel R.D. [UNESP] (Springer Nature, 2018)
Leishmania infantum is an etiologic agent of visceral leishmaniasis. This disease is a neglected disease that can be fatal if not treated and additionally, the few therapeutic option present several drawbacks, including difficult route of administration and toxicity, which turn the search for new therapeutic alternatives necessary. Herein, we evaluated the leishmanicidal in vitro activity of the solanum extract from Solanum lycocarpum A. St.-Hil., Solanaceae, and the isolated alkaloids solasodine, solamargine and solasonine against promastigotes and intracellular amastigotes of L. infantum. Solasodine (IC50-pro = 4.7 μg/ml; IC50-ama = 10.8 μg/ml) and solamargine (IC50-pro = 8.1 μg/ml; IC50-ama = 3.0 μg/ml) exhibited interesting leishmanicidal ativity. Solasonine was approximately four-times (Selective Index 3.7) more selective to the parasite than to the host cells. This data suggest that solasonine might be considered as a potential drug candidate for leishmaniasis treatment.
Keywords: Glycoalkaloids; Neglected disease; Solamargine; Solasodine; Solasonine; Visceral leishmaniasis